Manifestations of Tuberous Sclerosis Complex: The Experience of a Provincial Clinic. (7th November 2016) - Wilbur, Colin; Sanguansermsri, Chinnuwat; Chable, Hedi; Anghelina, Mihaela; Peinhof, Sharon; Anderson, Kelly; Steinbok, Paul; Singhal, Ash; Datta, Anita; Connolly, Mary B.
Abstract: Background: Tuberous sclerosis complex (TSC) is a neurocutaneous disorder with a wide spectrum of manifestations. Recent consensus recommendations stress the importance of multidisciplinary management of children with TSC. The objective of this study was to examine the manifestations of TSC at a large referral centre to determine the care needs of this population. Methods: A retrospective, systematic chart review was performed of children with TSC managed at British Columbia Children's Hospital. Patients were identified through epilepsy and clinical neurophysiology databases. Results: The study population comprised 81 patients, born between 1987 and 2014, who were a median of 10 years (range, 0.2-23.2) at most recent follow-up. Epilepsy occurred in 91% of patients, including 32% with a history of infantile spasms. Nineteen patients underwent epilepsy surgery, nine (47%) of whom were seizure-free at most recent follow-up. Overall, 61% of epilepsy patients had been seizure-free for at least 1 year at the time of last follow-up. Neuropsychiatric disorders were diagnosed in 49% of children, with autism (25%), attention deficit hyperactivity order (19%) and anxiety (16%) being the most common. Cardiac rhabdomyomata occurred in 35% of children and renal angiomyolipomas were seen in 43%. A total of 91% had skin manifestations. Conclusion: This study outlines the multisystem manifestations of TSC, observed through a large pediatric referral center. Epilepsy and neuropsychiatric disorders are the major source of morbidity in this age group and provide many challenges to the treating clinician. Because a subset of the study population is still quite young, the prevalence of neuropsychiatric disorders is likely underestimated. RÉSUMÉ: Manifestations du complexe de la sclérose tubéreuse : l'expérience d'une clinique provinciale. Contexte: La sclérose tubéreuse (ST) est une maladie neurocutanée comportant un large éventail de manifestations. Des recommandations consensuelles récentes ont souligné l'importance de la prise en charge multidisciplinaire des enfants atteints de ST. Le but de cette étude était d'examiner les manifestations de la ST chez les patients fréquentant un important centre de référence afin de déterminer quels sont les soins dont cette population a besoin. Méthodologie: Nous avons effectué une revue rétrospective systématique des dossiers d'enfants atteints de ST traités au Children's Hospital de la Colombie Britannique. Les patients ont été identifiés dans les bases de données contenant des renseignements sur l'épilepsie et la neurophysiologie. Résultats: Quatre-vingt-un patients nés entre 1987 et 2014, dont l'âge médian était de 10 ans (écart de 0, 2 à 23, 2) au moment de la plus récente visite de suivi, ont été identifiés. Quatre-vingt-onze pour cent des patients présentaient de l'épilepsie, dont 32% avaient une histoire de spasmes infantiles. Dix-neuf patients ont subi une chirurgie pour épilepsie, dont 9 (47%) n'ont pas présenté de crises après la chirurgie, selon l'information consignée au dossier à la plus récente visite de suivi et 61% des patients épileptiques n'avaient pas présenté de crise au cours de la dernière année. Des troubles neuropsychiatriques ont été diagnostiqués chez 49% des enfants, dont les plus fréquents étaient l'autisme (25%), le trouble du déficit de l'attention avec ou sans hyperactivité (19%) et un trouble anxieux (16%). Trente-cinq pour cent des enfants étaient porteurs de rabdomyomes cardiaques et 43% d'angiomyolipomes rénaux. Dans l'ensemble, 91% présentaient des manifestations cutanées. Conclusions: Cette étude décrit les manifestations multisystémiques de la ST observées dans un grand centre pédiatrique de référence. L'épilepsie et les troubles neuropsychiatriques sont la source majeure de morbidité dans ce groupe d'âge et de défis importants pour le médecin traitant. La prévalence des troubles neuropsychiatriques est vraisemblablement sous-estimée parce qu'une partie de la population étudiée est encore jeune.